Sevilla, Spain. The chalcolithic mega-site of Valencina de la Concepción (Sevilla), Spain. Results of the fieldwork from 2018 to 2020 - Schuhmacher, Thomas X.; Falkenstein, Frank; Mederos Martín, Alfredo; Ostermeier, Nils; Acero, Charles Bashore; El Dana, Natalie (e-Forschungsberichte des DAI, 2022)
The chalcolithic site of Valencina de la Concepción is located in Andalusia, in southern Spain, on the western edge of the Lower Guadalquivir river basin. The settlement area and a contemporaneous necropolis extend over more than 460 ha, constituting the largest site among a series of chalcolithic mega-sites located throughout the southwest of the Iberian Peninsula. The project focuses on the history of the chalcolithic settlement of Valencina de la Concepción. The investigations include excavations and field surveys on the agricultural land in the northern area of the archaeological site. Through geomagnetic surveys ten different lines of ditches, forming a total of five different enclosures and a sixth, smaller one could be detected. Besides ditches and pits, six dwelling structures and workshops, partially dug into the geological base, are being excavated. The available information and radiocarbon dates from the ditches and excavated structures indicate a continuous occupation of the settlement of Valencina from 3300/3200 to 2200 cal. BC and allow a hypothetical reconstruction of the different enclosures. Between 2300 and 2200 cal. BC settlement activity in Valencina came almost to an end. There are only a few remains indicating occupation of the site during a final stage of the Early Bronze Age, between 1900 and 1700 cal. BC.